The ALMA REBELS Survey: specific star formation rates in the reionization era. Issue 1 (17th August 2022) - Topping, Michael W; Stark, Daniel P; Endsley, Ryan; Bouwens, Rychard J; Schouws, Sander; Smit, Renske; Stefanon, Mauro; Inami, Hanae; Bowler, Rebecca A A; Oesch, Pascal; Gonzalez, Valentino; Dayal, Pratika; et al.
ABSTRACT: We present specific star formation rates (sSFRs) for 40 ultraviolet (UV)-bright galaxies at z ∼ 7–8 observed as part of the Reionization Era Bright Emission Line Survey (REBELS) Atacama Large Millimeter/submillimeter Array (ALMA) large programme. The sSFRs are derived using improved star formation rate (SFR) calibrations and spectral energy distribution (SED)-based stellar masses, made possible by measurements of far-infrared (FIR) continuum emission and [C ii ]-based spectroscopic redshifts. The median sSFR of the sample is 18_-5^+7 Gyr −1, significantly larger than literature measurements lacking constraints in the FIR, reflecting the larger obscured SFRs derived from the dust continuum relative to that implied by the UV+optical SED. We suggest that such differences may reflect spatial variations in dust across these luminous galaxies, with the component dominating the FIR distinct from that dominating the UV. We demonstrate that the inferred stellar masses (and hence sSFRs) are strongly dependent on the assumed star formation history in reionization-era galaxies. When large sSFR galaxies (a population that is common at z > 6) are modelled with non-parametric star formation histories, the derived stellar masses can increase by an order of magnitude relative to constant star formation models, owing to the presence of a significant old stellar population that is outshined by the recent burst. The [C ii ] line widths in the largest sSFR systems are often very broad, suggesting dynamical masses capable of accommodating an old stellar population suggested by non-parametric models. Regardless of these systematic uncertainties among derived parameters, we find that sSFRs increase rapidly toward higher redshifts for massive galaxies (9.6 < log ( M * /M⊙ ) < 9.8), evolving as (1 + z ) 1.7 ± 0.3, broadly consistent with expectations from the evolving baryon accretion rates.